2021
DOI: 10.51244/ijrsi.2021.8706
|View full text |Cite
|
Sign up to set email alerts
|

Ethnographic and Costume Regalia of Paari-gbiele Festival in Northern Ghana

Abstract: Paari-gbiele is an annual post-harvest festival celebrated by the Sisaala indigenes of Tumu Traditional Area in the Sissala East Municipality of the Upper West Region of northern Ghana. It is celebrated annually to mark the end of successful farming season. It also serves as a momentous occasion for the glorification of the almighty God and the revered agriculturally related deities of the indigenes of Tumu Traditional Area for their protection and blessings of seasonal bumper harvests to the farmers. Paari-gb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Navei (2021) concurs that Kanton was a famous hunter and one of the leading known warriors who fought and succeeded the slave raiders in Sisaala land during the era of the slave trade. With such unbroken records of achievements, the people of Tumu, led by the Kanton family, have set aside 29 th January yearly to commemorate his heroic and hunting prowess that contributed immensely to the development of the Sisaala enclave (Navei, 2021). As a heroic icon, Kanton's annual commemorative event always calls for the adornment of war costume regalia for the performance of bayilla (war dance) which he once actively participated in.…”
Section: Ceremonial Costume Art Of Fuowie Nasolomentioning
confidence: 99%
See 4 more Smart Citations
“…Navei (2021) concurs that Kanton was a famous hunter and one of the leading known warriors who fought and succeeded the slave raiders in Sisaala land during the era of the slave trade. With such unbroken records of achievements, the people of Tumu, led by the Kanton family, have set aside 29 th January yearly to commemorate his heroic and hunting prowess that contributed immensely to the development of the Sisaala enclave (Navei, 2021). As a heroic icon, Kanton's annual commemorative event always calls for the adornment of war costume regalia for the performance of bayilla (war dance) which he once actively participated in.…”
Section: Ceremonial Costume Art Of Fuowie Nasolomentioning
confidence: 99%
“…In contemporary Tumu, traditional cultural practices have notoriously survived the associated negative effects of post-colonialism that are generally witnessed in Africa (Ghana) to the extent that the place identity of Tumu is well-defined, preserved, and promoted during traditional cultural ceremonies. While previous studies have generally noted that colonialism, Western education, and globalisation have adversely affected youth participation in traditional African cultural practices (Ofori et al, 2021;Dennis, 2018;Sibani, 2018), it is observed that a good number of the youth in the Tumu Traditional area are noted for their active participation in traditional cultural practices, particularly during the celebration of the Paari-gbiele (post-harvest) festival (Figure 1 A, B, C & D) in this contemporary era (Navei, 2021). This creates a contraction, and for that matter, a contextual lacuna that needs further examination to reveal the motivation behind youth cultural activism in contemporary Tumu.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations